Warehousing System Analysis with Fuzzy Tsukamoto Method and Fuzzy C-Mean Case Study PT. Kemindo Parama Mandiri - Iis Hikmah Kurniani; Asep Endih Nurhidayat (Teknik Industri Universitas Indraprasta PGRI, 2022)
Warehouse stock management is still poor, starting from the stock retention period is too long and the stock recording is still manual until there is a difference between the actual warehouse stock and the stock in the recording data. The result of the calculation analysis from Fuzzy Tsukamoto Recording the actual stock data and the recorded stock obtained the calculation result with this method obtained a value of 79.30 with good valuation. Lot arrangement no. the calculation result with this method obtains a value of 73.92 with a good valuation. The result of warehouse management calculation with this method obtained a value of 78.54 with a good evaluation. Computational analysis results from Fuzzy C-Mean Recording for actual stock data and recorded stock After repeated 3 times the error value = 0.17 approaches 0.1 and the selected cluster center is cluster 3 reporting stock data that needs to be improved. Structuring lot number After 5 iterations, the error value = 0.10 approaches 0.1 and the selected cluster center is cluster 2, the data item according to the lot that needs to be corrected. Warehouse management After 5 iterations, the error value = 0.04 is smaller than 0.1 and the selected cluster center is cluster 1 receiving and removing the goods that need to be repaired. record data using the system to be more tidy and avoid data differences between actual stock and stock on the system, lot arrangement by making lot number data report useful for item identity, facilitate search, collect expiration date data of goods with time period and goods entry and exit system on warehouse and warehouse management is increasing by implementing kaizen, 5S and maintaining K3 in the warehouse area so that security and procedures are expected to run well if the warehouse management is good then the system transaction can run well because storage warehouse is the most important part of the company